2016
DOI: 10.1007/s10195-016-0411-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors preventing kneeling in a group of pre-educated patients post total knee arthroplasty

Abstract: BackgroundDifficulties in kneeling, one of the poorest scoring functional outcomes post total knee arthroplasty (TKA),have been attributed to a lack of patient education. This is the first study to investigate specific factors affecting a patient’s perceived ability to kneel post TKA, following exposure to a preoperative kneeling education session.Materials and methodsA cross-sectional study was conducted following TKA with patients who had been educated about kneeling prior to the operation. Patients complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…22 Additionally, preoperative patient education about kneeling after TKA has not resulted in substantial improvement in the proportion of patients who report kneeling ability after TKA. 24 Therefore, patient perceptions of which activities are acceptable after TKA should be assessed to allow for maximal surgical benefit.…”
Section: Biomechanics Of Kneelingmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Additionally, preoperative patient education about kneeling after TKA has not resulted in substantial improvement in the proportion of patients who report kneeling ability after TKA. 24 Therefore, patient perceptions of which activities are acceptable after TKA should be assessed to allow for maximal surgical benefit.…”
Section: Biomechanics Of Kneelingmentioning
confidence: 99%
“…3,27 However, knee stability has not been implicated in the inability to kneel. 24 Psychological factors and patient education are increasingly reported as primary drivers of patients' inability to kneel or dissatisfaction with kneeling after surgery. 4,28 Given the lack of consensus regarding factors affecting kneeling and outcomes associated with kneeling after TKA, we evaluated the available empirical and kinematic data to guide postoperative recommendations.…”
mentioning
confidence: 99%
“…The novelty of current study is that giving an attention to healthcare professionals as well as TKA patients regarding an important knee function question, which remains improperly answered because of limited studies in the literature [11,12]. As the question remains before and after TKA'' is kneeling safe and viable function after TKA?''…”
Section: Discussionmentioning
confidence: 99%
“…A randomised controlled trial found that a 30-minute physiotherapy intervention delivered at 6 weeks post-surgery improved patient-reported kneeling ability at 12 months after unicompartmental knee replacement [15]. A cohort study suggests that preoperative kneeling advice may improve post-operative kneeling ability [28].…”
Section: Discussionmentioning
confidence: 99%